2017
DOI: 10.1002/2017gl074665
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for pollution‐influenced selective uptake contributing to biogenic secondary organic aerosols in the southeastern U.S.

Abstract: During the 2013 Southern Oxidant and Aerosol Study, aerosol mass spectrometer measurements of submicron mass and single particles were taken at Look Rock, Tennessee. Their concentrations increased during multiday stagnation events characterized by low wind, little rain, and increased daytime isoprene emissions. Organic mass (OM) sources were apportioned as 42% “vehicle‐related” and 54% biogenic secondary organic aerosol (bSOA), with the latter including “sulfate‐related bSOA” that correlated to sulfate (r = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 84 publications
(138 reference statements)
3
22
0
Order By: Relevance
“…The LRK and CTR sites are influenced by the Bermuda‐Azores High in summer, with warm humid air moving northward and northeastward from the Gulf of Mexico into the interior of the continent (Davis et al, ). The aerosol particle concentrations accumulated for periods of several days with low wind and little precipitation before being washed out (Liu et al, ). The precipitation events overlapped 70% of the time at the two sites during SOAS, synchronizing particle removal and thus contributing to the correlation of the time series of concentrations (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The LRK and CTR sites are influenced by the Bermuda‐Azores High in summer, with warm humid air moving northward and northeastward from the Gulf of Mexico into the interior of the continent (Davis et al, ). The aerosol particle concentrations accumulated for periods of several days with low wind and little precipitation before being washed out (Liu et al, ). The precipitation events overlapped 70% of the time at the two sites during SOAS, synchronizing particle removal and thus contributing to the correlation of the time series of concentrations (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The high m / z 44 level suggested that this factor likely includes substantial contributions from secondary sources. LRK‐Factor82 and CTR‐Isoprene‐OA have been associated with isomeric isoprene epoxydiols (IEPOX; Liu et al, ; Xu et al, ). This factor contributed 20% to OM at LRK and 18% to OM at CTR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations